Relevance of Ancient Chinese Wine Ware Representation Design and Cultural Characteristics Based on Machine Learning and Semiotic Theory. (28th July 2022) - Wang, Weifan; Wei, Jie; Xu, Han; Zhang, Yudian; Chen, Han
Abstract : Wine has an indispensable position in the ancient national food culture. Among them, wine vessels, as material carriers, are the core of ancient national wine culture, reflecting social functions, plastic arts, craft production, customs, habits, etc., and therefore are also the concrete expression of spiritual and institutional culture. Ancient ethnic traditional drinking vessels are not only a comprehensive manifestation of the precious material cultural heritage but also of the ancient spiritual culture of the nation. Through the study of the representational design and cultural characteristics of ancient ethnic traditional drinking vessels and the aesthetic tendencies they reflect, we can see the unique philosophy of life and the spiritual reverence of ancient peoples. Although these traditional ancient ethnic drinking vessels are now gradually marginalized and some have completely withdrawn from the historical stage, their spiritual and cultural value has increased rather than decreased. This paper explores the representational design and cultural characteristics of ancient traditional drinking vessels and the aesthetic tendencies they reflect and analyzes the correlation between them using ML methods and semiotic theory, to get a glimpse of the unique talent and wisdom of the ancients in aesthetic creation and gain new design inspiration from them.